2006
DOI: 10.1159/000092448
|View full text |Cite
|
Sign up to set email alerts
|

Palliative In-Patient Cancer Treatment in an Anthroposophic Hospital: II. Quality of Life during and after Stationary Treatment, and Subjective Treatment Benefits*

Abstract: There is an increasing demand for comprehensive forms of palliative cancer care, meeting physical as well as emotional, cognitive, spiritual and social needs. Therapy programs of anthroposophic hospitals are aimed at improving health and quality of life (QoL) at these levels. However, data on the influence of these programs on QoL of patients with advanced cancer are scarce. Patients and Methods: 144 in-patients with advanced epithelial cancers were treated at the anthroposophic Lukas Klinik, Arlesheim, Switze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 57 publications
(70 reference statements)
1
27
0
4
Order By: Relevance
“…9,10,13 Previous studies have found beneficial effects of AM therapies on anxiety in cancer patients. 51,52 The present study is the first to demonstrate improvement of patients with anxiety disorders under AM treatment.…”
Section: Discussionmentioning
confidence: 56%
“…9,10,13 Previous studies have found beneficial effects of AM therapies on anxiety in cancer patients. 51,52 The present study is the first to demonstrate improvement of patients with anxiety disorders under AM treatment.…”
Section: Discussionmentioning
confidence: 56%
“…Diverse klinische Studien konnten belegen, dass stationäre Behandlungen mit einem naturheilkundlichen [10,11,12,13,14,15] oder integrativen [16,17,18,19] Ansatz zu einer wesentlichen und nachhaltigen Verbesserung der gesamten LQ führen.…”
Section: Diskussionunclassified
“…Die vergleichbar niedrige Anzahl von stationären Patienten (n = 144) in der Erhebung von Heusser at al. [19] lässt auf eine ähnliche Problematik in der Rekrutierung von stationären Patienten in den anthroposophischen Kliniken in der Schweiz schliessen.…”
Section: Diskussionunclassified
See 2 more Smart Citations